Inteins in pathogenic fungi: a phylogenetic tool and perspectives for therapeutic applications - Theodoro, Raquel Cordeiro [UNESP] (2009)
Inteins or internal proteins are coding sequences that are transcribed and translated with flanking sequences (exteins). After translation, the inteins are excised by an autocatalytic process and the host protein assumes its normal conformation and develops its expected function. These parasitic genetic elements have been found in important, conserved proteins in all three domains of life. Most of the eukaryotic inteins are present in the fungi kingdom and the PRP8 intein is one of the most widespread inteins, occurring in important pathogens such as Cryptococcus neoformans (varieties grubii and neoformans), Cryptococcus gattii, Histoplasma capsulatum and Paracoccidioides brasiliensis. The knowledge of conserved and non-conserved domains in inteins have opened up new opportunities for the study of population variability in pathogenic fungi, including their phylogenetic relationships and recognition or diagnoses of species. Furthermore, inteins in pathogenic fungi should also be considered a promising therapeutic drug target, since once the autocatalytic splicing is inhibited, the host protein, which is typically vital, will not be able to perform its normal function and the fungal cell will not survive or reproduce.